An Ayurvedic Approach to Improving Anti-Mullerian Hormone: Essential Preparation for Assisted Reproductive Technique (International Journal of Ayurveda and Pharma Research, 2025)
Low levels of Anti-Mullerian Hormone (AMH) are often associated with hormonal imbalances that lead to reduced ovarian reserve and infertility. This condition is commonly marked by increased follicle-stimulating hormone (FSH), diminished AMH, and a decreased antral follicle count (AFC), which collectively lower the chances of conception. AMH, produced by granulosa cells within preantral and antral follicles, is a key indicator of ovarian reserve and an important predictor of how the ovaries respond to stimulation. Its strong link to follicle development makes it a valuable tool for assessing fertility potential. Women with low AMH levels undergoing in vitro fertilization (IVF) often experience poor outcomes, and many are left with the option of donor egg IVF as their only choice. Ayurvedic medicine provides holistic treatment options for infertility, by enhancing the body’s natural ability to restore hormonal balance, improve ovarian health, and boost oocyte quality, offering hope to those facing fertility challenges. The present case report document the efficacy of an Ayurvedic treatment protocol in improving the AMH value. The patient had undergone Shamana and Sodhana therapies and on follow up marked improvement in AMH level was found making her eligible for ART with her own egg.